Stroke incidence in heart failure and atrial fibrillation: population cohort study - Jones, N; Smith, M; Lay-Flurrie, S; Yang, Y; Hobbs, R; Taylor, C (Royal College of General Practitioners, 2025)
Background: Heart failure (HF) is a risk factor for stroke among people with atrial fibrillation (AF). Prognosis following a HF diagnosis is often poor, but this is not accounted for in existing stroke risk scores. Aim: To examine stroke incidence in people with HF and AF compared to AF alone, considering the competing risk of death. Design and setting: Population-based cohort study. Methods: We identified 2,381,941 people aged ≥45 years in the Clinical Practice Research Datalink (2000-2018). HF and AF were included as time-varying covariates; 69,575 had HF and AF, 141,562 had AF alone and 91,852 had HF alone. We report hazard ratios for first stroke using Cox and Fine and Gray models. Results: Over median follow-up of 6.62 years, 93,665 people (3.9%) had a first stroke and 314,042 (13.2%) died. Over half (51.3%) of those with HF and AF died. In the fully-adjusted Cox model, relative stroke risk was highest among people with AF alone (HR 2.43, 95%CI: 2.38-2.48) than HF and AF (HR 2.20, 95%CI: 2.14-2.26). In a Fine and Gray model accounting for all-cause mortality, the relative risk of stroke was similar for people with AF alone (HR 2.38, 95%CI: 2.33-2.43), but there was significant attenuation among those with HF and AF (HR 1.48, 95%CI: 1.44-1.53). Conclusion: HF is an aetiological risk factor for stroke yet its prognostic significance is reduced by the high incidence of death. Use of the CHA2DS2VASc score may over-estimate stroke incidence in some people with HF, particularly those with a poor prognosis.